Changing precipitation patterns in far-western Nepal in relation to landslides in Bajhang and Bajura districts - Nayava, Janak Lal; Bhusal, Jagat Kumar; Paul, Jonathan D.; Buytaert, Wouter; Neupane, Bhanu; Gyawali, Januka; Poudyal, Saugat (Geographical Journal of Nepal, 2022)
The geologically young terrains of the Nepal's Lesser Himalaya are strongly affected by the multiple and interrelated geo-hazards of landslides, floods, and debris torrents. One of the main factors that trigger these hazards is the duration and intensity of monsoon rainfall. Here, we interrogate precipitation data for a variety of different periods, the longest of which comprises 40 years (1977-2017) of annual rainfall data, for 17 rainfall stations in far-western Nepal. The average rainfall over the past 10 years (2007-2017) was found to be declining for most stations. The summer monsoon season (i.e. June to September) accounts for 70–80% of the total annual rainfall, and is critical for agricultural production; but the vast majority of floods and landslides also occur during this time. Changes in daily rainfall magnitude and frequency are analysed. The intensity of rainfall during monsoon time was found to increase by over 100% in the past 40 years, with this change especially pronounced in 2008. The variation of intensities of rainfall in relation to landslides at different elevations has also been explored. We found that rainfall intensity increased by 40–60% over an increase in elevation from 1 to 2 km in the study area of the Bajedi landslide in far-western Nepal.